The Renewability Indicator and Cumulative Degree of Perfection for Gamboeng Tea; Part.2, Exergy Calculation of Tea Factory - Teuku Beuna Bardant; Muthia Syafika Haq; Arief Ameir Rahman Setiawan; Sugeng Harianto; Joko Waluyo; Adhi Irianto Mastur; Annisa Dieni Lestari; Anny Sulaswatty; Sujarwo Sujarwo; Nino Rinaldi; Edi Iswanto Wiloso (Research Center for Chemistry - LIPI, 2018)
Renewability Indicator (RI) and Cumulative Degree of Perfection (CDP) were used to observe sustainability of Gamboeng Tea. The assessment then compared with black tea process in Black Sea Region in Turkey from the previous study. Calculation of exergy for Gamboeng fresh tea leaf had already described in Part.1. Since the main process for both production was drying, then tropical humid climate in Gamboeng is the main challenge to increase efficiency, and thus, renewability. This second part described the significant improvement of renewability had applied in Gamboeng by using wood pellet in rotary pannier. Further recommended improvement were by installing better humidity detector and connected to the process control so the process can adapt the ambient change which the relative humidity can be varied from 65% and up to 92%.